1993
DOI: 10.1111/j.1440-1827.1993.tb03232.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a human lung adenocarcinoma cell line (LC‐2/ad) producing α1‐antitrypsin in vitro

Abstract: A new human cell line, LC‐2/ad was established from pleural effusion of pulmonary adenocarcinoma of a 51 year old Japanese female. The LC‐2/ad cells exhibit an epithelial appearance and a tendency to form small domes as observed with phase‐contrast microscopy. The modal chromosome number was 53–56. Plating efficiency and doubling time were 6.8% and 58 h, respectively (32th passage). Immunocytochemlcally, the cells were strongly positive for CEA and cytokeratins including cytokeratin no. 18 which is present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The original report indicated that the LC-2 ⁄ ad cells were positive for an adenocarcinoma marker, cytokeratin 18. (23) In addition, we detected surfactant protein, an aspartate proteinase, Napsin A, and CEA expression in the xenograft tumor (Fig. 4a).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The original report indicated that the LC-2 ⁄ ad cells were positive for an adenocarcinoma marker, cytokeratin 18. (23) In addition, we detected surfactant protein, an aspartate proteinase, Napsin A, and CEA expression in the xenograft tumor (Fig. 4a).…”
Section: Discussionmentioning
confidence: 86%
“…LC2 ⁄ ad cells at 5.0 9 10 6 were subcutaneously inoculated to 8-week-old athymic nude mice (Clea Japan). (23) Vandetanib was administered once daily as a homogeneous suspension by oral gavage at a dosage of 50 mg ⁄ kg body weight. (24) The tumor volume was calculated as the product of a scaling factor (p ⁄ 6) and the tumor length, width and height.…”
Section: Methodsmentioning
confidence: 99%
“…Similar findings have been reported by a number of other research groups. These SPI include α1‐proteinase inhibitor (αPI), 16–21 α1‐antichymotrypsin (αACT), 9 plasminogen activator inhibitor (PAI)‐1 and PAI‐2, 19,22 squamous cell carcinoma (SCC) antigen, 23 pancreatic secretory trypsin inhibitor (PSTI), 24,25 amyloid β protein precursor (APP), 26–29 tissue factor pathway inhibitor (TFPI)‐1 and TFPI‐2, 30,31 secretory leukocyte proteinase inhibitor (SLPI) 31,32 and hepatocyte growth factor activator inhibitor type 1 (HAI‐1) 33,34 and HAI‐2 35–37 . These SPI can be classified into several subgroups according to their molecular structures and mechanisms of proteinase inhibition: (i) serpin‐type SPI, such as αPI, αACT, PAI‐1, PAI‐2 and SCC antigen; (ii) Kunitz‐type SPI, such as APP, TFPI‐1, TFPI‐2, HAI‐1 and HAI‐2; (iii) Kazal‐type SPI, such as PSTI and SLPI.…”
Section: Production Of Serine Proteinase Inhibitors By Tumor Cells Anmentioning
confidence: 99%
“…In the current study, we examined the molecular mechanisms of hBD‐2 expression in vitro . To perform the present study, we used a human airway cell line, LC‐2/ad, which was established from pleural effu‐sion of pulmonary adenocarcinoma and exhibits an epithelial appearance 14 …”
Section: Introductionmentioning
confidence: 99%